The Impact of Social Determinants of Health on 30 and 90-Day Readmission Rates After Spine Surgery. (2nd March 2022) - Mohanty, Sarthak; Lad, Meeki K.; Casper, David; Sheth, Neil P.; Saifi, Comron
Abstract : Background: Since its 2012 inception, the U.S. Centers for Medicare & Medicaid Services Hospital Readmissions Reduction Program (HRRP) has espoused cost-effective health-care delivery by financially penalizing hospitals with excessive 30-day readmission rates. In this study, we hypothesized that socioeconomic factors impact readmission rates of patients undergoing spine surgery. Methods: In this study, 2, 830 patients who underwent a spine surgical procedure between 2012 and 2018 were identified retrospectively from our institutional database, with readmission (postoperative day [POD] 0 to 30 and POD 31 to 90) as the outcome of interest. Patients were linked to U.S. Census Tracts and ZIP codes using the Geographic Information Systems (ArcGIS) mapping program. Social determinants of health (SDOH) were obtained from publicly available databases. Patient income was estimated at the Public Use Microdata Area level based on U.S. Census Bureau American Community Survey data. Univariate and multivariable stepwise regression analyses were conducted. Significance was defined as p < 0.05, with Bonferroni corrections as appropriate. Results: Race had a significant effect on readmission only among patients whose estimated incomes were <31, 650 (χ 2 = 13.4, p < 0.001). Based on a multivariable stepwise regression, patients with estimated incomes of <31, 000 experienced greater odds of readmission by POD 30 compared with patients with incomes of >62, 000; the odds ratio (OR) was 11.06 (95% confidence interval [CI], 6.35 to 15.57). There were higher odds of 30-day readmission for patients living in neighborhoods with higher diabetes prevalence (OR, 3.02 [95% CI, 1.60 to 5.49]) and patients living in neighborhoods with limited access to primary care providers (OR, 1.39 [95% CI, 1.10 to 1.70]). Lastly, each decile increase in the Area Deprivation Index of a patient's Census Tract was associated with higher odds of 30-day readmission (OR, 1.40 [95% CI, 1.30 to 1.51]). Conclusions: Socioeconomically disadvantaged patients and patients from areas of high social deprivation have a higher risk of readmission following a spine surgical procedure. Level of Evidence: Prognostic Level IV . See Instructions for Authors for a complete description of levels of evidence.